Investigating the cardiovascular effects of antiretroviral drugs in a lean and high fat/sucrose diet rat model of obesity : an in vivo and ex vivo approach - Everson, Frans Pieter (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.